Developing, implementing and evaluating a simulation learning package on post-partum haemorrhage for undergraduate midwifery students in KwaZulu-Natal* - Hafaza B. Amod; Petra Brysiewicz (AOSIS, 2017)
Background: The training of undergraduate midwifery students to identify and manage post-partum haemorrhage, is an essential skill in midwifery. Aim: The aim of this study was to develop, implement and evaluate a simulation learning package (SLP) on post-partum haemorrhage for undergraduate midwifery students using high fidelity simulation without risks to real-life patients. Methods: An exploratory sequential mixed methodology was used in this study. The study was made up of three phases namely; the development, implementation and evaluation of the learning package. The research participants were fourth year baccalaureate of nursing midwifery students and midwifery experts involved in teaching midwifery. Data was collected using an evaluation checklist for experts, a student satisfaction survey and focus group sessions. Quantitative data were analysed using SPSS Version 23.0 and the qualitative data was analysed using content analysis as described by Graneheim and Lundman(2004). Results: The evaluation checklist for experts revealed that the developed SLP was considered suitable for undergraduate students. It encouraged active learning, teamwork and accommodated diverse learning styles. The package was easy to use and offered opportunities for student feedback. The student satisfaction survey revealed that the pre-simulation support received was adequate and helpful, and the post simulation outcomes showed that using high fidelity simulation improved clinical skills, knowledge, critical thinking, self-confidence and satisfaction. The focus group sessions revealed that the SLP was an innovative and interactive method of learning; it improved the student's perception of their clinical competence, stimulated critical thinking and increased self-confidence. Conclusion: A simulation learning package, that uses high fidelity simulation, can be an innovative and interactive method to teach midwifery emergencies.